2003
DOI: 10.1128/aem.69.4.2087-2093.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Equine Cecal Bacteria Producing Amines in an In Vitro Model of Carbohydrate Overload

Abstract: Acute laminitis has been associated with the overgrowth of gram-positive bacteria within the equine hindgut, causing the release of factor(s) leading to ischemia-reperfusion of the digits. The products of fermentation which trigger acute laminitis are, as yet, unknown; however, vasoactive amines are possible candidates. The objectives of this study were to use an in vitro model of carbohydrate overload to study the change in populations of cecal streptococci and lactobacilli and to establish whether certain sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 38 publications
4
72
1
8
Order By: Relevance
“…No entanto, KIENZLE (1994) sugerem que esse limite é inferior a 3,5g. O excesso de amido no intestino grosso seleciona rapidamente espécies de bactérias amilolíticas (JULLIAND et al, 2001;BAILEY et al, 2003), o que resulta na fermentação do amido e produção de grandes quantidades de ácido láctico (GARNER et al, 1978;GOODSON et al, 1988). O ácido láctico causa irritação no epitélio de revestimento intestinal, sobrepõe a capacidade de tamponamento normal do intestino e diminui o pH do seu conteúdo (PAGAN, 1998).…”
Section: Resultsunclassified
“…No entanto, KIENZLE (1994) sugerem que esse limite é inferior a 3,5g. O excesso de amido no intestino grosso seleciona rapidamente espécies de bactérias amilolíticas (JULLIAND et al, 2001;BAILEY et al, 2003), o que resulta na fermentação do amido e produção de grandes quantidades de ácido láctico (GARNER et al, 1978;GOODSON et al, 1988). O ácido láctico causa irritação no epitélio de revestimento intestinal, sobrepõe a capacidade de tamponamento normal do intestino e diminui o pH do seu conteúdo (PAGAN, 1998).…”
Section: Resultsunclassified
“…It appears that feeding GSE has either decreased the amount of starch entering (the caecum) or changed the nature of fermentation in the caecum. Fermentation of starch in the hindgut is associated with an increase in populations of Gram-positive bacteria (Bailey et al, 2003). Jayaprakasha et al (2003) found Gram-positive bacteria were completely inhibited by GSE treatment (850 to 1000 p.p.m.).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite its importance for intestinal lactic acid bacteria and bifidobacteria, information about the bacterial flora of the organisms in feces and/or intestinal contents of horses is limited, compared with pet animals and farm animals (Mentula et al, 2005;Orban et al, 1997;Petr and Rada, 2001;Rada et al, 2006). Little has been known about lactic acid bacteria (Bailey et al, 2003;Yuyama et al, 2004), and particularly bifidobacteria (Mitsuoka and Kaneuchi, 1977). Moreover, all the knowledge has derived from data obtained only by the culturing technique.…”
mentioning
confidence: 99%